The Effect of Nature Learning Method on the Improvement of Poetry Text Writing Skills in Class X Students - Ukhra, Aura Radhiatul; Trisfayani, Trisfayani; Safriandi, Safriandi (Continuous Education: Journal of Science and Research, 2024)
This study aims to describe the effect of the Nature Learning method in improving the poetry writing skills of 10th grade students at SMAN Modal Bangsa Arun, as well as to determine student participation in poetry learning using this method. This research uses a quantitative method with a pretest-posttest control group design. The research sample consists of two groups: the experimental group, which uses the Nature Learning method, and the control group, which uses conventional learning methods. The data analysis technique involves collecting poetry writing skills data through pretest and posttest writing tests, while data on student participation in the experimental group is collected through a questionnaire. Poetry writing skills data are analyzed using a t-test to see if there are significant differences between the two groups, and student participation data is calculated using a formula to obtain results on student participation after the Nature Learning method is applied. The results show that there was a significant improvement in poetry writing skills in the experimental group compared to the control group. This was obtained from the hypothesis test results using a t-test, with a significance value (2-tailed) of 0.000, which is smaller than the common significance level of 0.05. This indicates that the Nature Learning method has a significant effect on improving poetry writing skills in 10th grade students at SMA Negeri Modal Bangsa Arun. Students who learned through the Nature Learning method showed higher creativity and better sensitivity to the use of language and imagery in poetry.